2018
DOI: 10.1161/atvbaha.117.309565
|View full text |Cite
|
Sign up to set email alerts
|

Apo A-I (Apolipoprotein A-I) Vascular Gene Therapy Provides Durable Protection Against Atherosclerosis in Hyperlipidemic Rabbits

Abstract: In rabbits with severe hyperlipidemia, transduction of vascular endothelial cells with an apo A-I-expressing HDAd yields at least 24 weeks of local apo A-I expression that durably reduces atherosclerotic lesion growth and intimal inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 94 publications
0
29
1
1
Order By: Relevance
“…53 So far, several interventional approaches targeting apoA-I have been developed 54, 55 and a few of them revealed beneficial effects against atherosclerosis in humans, 56 but none of these strategies have resulted in clinical use. A recent manuscript published in ATVB demonstrated that apoA-I vascular gene therapy targeting endothelial cells shows a protective effect against atherosclerosis in hyperlipidemic rabbits, 57 suggesting that increased apoA-I expression in the endothelium is atheroprotective. In addition, apoA-I mimetic peptides have been continuously developed in parallel with the investigation of its functionality in vivo .…”
Section: High-density Lipoproteinmentioning
confidence: 99%
“…53 So far, several interventional approaches targeting apoA-I have been developed 54, 55 and a few of them revealed beneficial effects against atherosclerosis in humans, 56 but none of these strategies have resulted in clinical use. A recent manuscript published in ATVB demonstrated that apoA-I vascular gene therapy targeting endothelial cells shows a protective effect against atherosclerosis in hyperlipidemic rabbits, 57 suggesting that increased apoA-I expression in the endothelium is atheroprotective. In addition, apoA-I mimetic peptides have been continuously developed in parallel with the investigation of its functionality in vivo .…”
Section: High-density Lipoproteinmentioning
confidence: 99%
“…Another approach to gene therapy may be that of transducing arterial endothelial cells with the helper dependent adenoviral (HdAd) vector expressing apoA-I [93]. High fat fed rabbits underwent bilateral carotid artery gene transfer, one artery receiving a control vector (Hd Null) and the other receiving an apoA-I expressing vector.…”
Section: Hdl Therapythe Coronary Atheroma Target (Figure 1)mentioning
confidence: 99%
“…Sustained expression of endothelial cells has been demonstrated upon intra-arterial delivery of HC-AdVs. Using this approach, significant improvement has been observed in high fat diet-fed rabbits [137]. Co-expression of Apo AI and the ATP-binding cassette subfamily A, member 1 (ABCA1) is feasible using HC-AdVs, and this combination can improve the cholesterol efflux from endothelial cells [138].…”
Section: Liver-directed Gene Supplementationmentioning
confidence: 99%